Development and validation of a standardized assessment instrument for discus throwing performance: A reliability study among high school students - Henjilito, Raffly; Zulkifli, Zulkifli; Yani, Ahmad; Setiawan, Budi Arif; Pardilla, Herli (SPORT TK-EuroAmerican Journal of Sport Sciences, 2026)
This study focused on creating and validating a dependable tool for assessing discus throw performance in secondary school students. The sample comprised 240 students (120 males, 120 females; aged 15-17) from 12 institutions, selected via stratified random sampling for skill and demographic representation. The assessment tool was developed with expert guidance and preliminary testing, incorporating five technical components: starting position, starting swing, movement across the circle, power position, and release-recovery. Statistical methods included the Intraclass Correlation Coefficient (ICC) via a two-way mixed-effects model, Cronbach’s alpha for internal consistency, test-retest reliability over two weeks, and Standard Error of Measurement (SEM) with bootstrapping to establish confidence intervals. The overall reliability of the instrument was excellent (ICC=0.89, 95% CI: 0.85-0.93). Notable internal consistency was found (Cronbach’s α = 0.87), coupled with strong test-retest reliability (r=0.91, p<0.001). Component analysis indicated the highest reliability in the power position (ICC=0.92) and the lowest in the initial swing (ICC= 0.86). A positive correlation existed between experience level and reliability measures (ICCs from 0.86 to 0.92). Gender analysis revealed comparable reliability for males (ICC=0.88) and females (ICC=0.90). The reliability among diverse components and demographics supports its use in both formative and summative assessments.